High Thermoelectric Performance in n‐Type Perylene Bisimide Induced by the Soret Effect. Issue 45 (13th September 2020) - Jiang, Qinglin; Sun, Hengda; Zhao, Duokai; Zhang, Fengling; Hu, Dehua; Jiao, Fei; Qin, Leiqiang; Linseis, Vincent; Fabiano, Simone; Crispin, Xavier; Ma, Yuguang; Cao, Yong
Abstract: Low‐cost, non‐toxic, abundant organic thermoelectric materials are currently under investigation for use as potential alternatives for the production of electricity from waste heat. While organic conductors reach electrical conductivities as high as their inorganic counterparts, they suffer from an overall low thermoelectric figure of merit ( ZT ) due to their small Seebeck coefficient. Moreover, the lack of efficient n‐type organic materials still represents a major challenge when trying to fabricate efficient organic thermoelectric modules. Here, a novel strategy is proposed both to increase the Seebeck coefficient and achieve the highest thermoelectric efficiency for n‐type organic thermoelectrics to date. An organic mixed ion–electron n‐type conductor based on highly crystalline and reduced perylene bisimide is developed. Quasi‐frozen ionic carriers yield a large ionic Seebeck coefficient of −3021 μV K −1, while the electronic carriers dominate the electrical conductivity which is as high as 0.18 S cm −1 at 60% relative humidity. The overall power factor is remarkably high (165 μW m −1 K −2 ), with a ZT = 0.23 at room temperature. The resulting single leg thermoelectric generators display a high quasi‐constant power output. This work paves the way for the design and development of efficient organic thermoelectrics by the rational control of the mobility of the electronic and ionic carriers. Abstract : An organic mixed‐ion–electron n‐type conductor based on highly crystalline and reduced perylene bisimide is developed, achieving a record ZT value of 0.23 that enables a quasi‐constant thermoelectric power output. This work paves the way for the design and development of efficient organic thermoelectrics by rational control of the mobility of the electronic and ionic carriers.